Electronic cigarette use and probable damage to the respiratory system: A systematic review (Research, Society and Development, 2024)
The objective of the present study is to analyze the literature to verify the existence of consequences caused by electronic cigarettes, as well as their possible effects on the respiratory system. A systematic literature review was carried out in the Google Scholar, Scielo, Pubmed and Lilacs databases, using the terms “electronic cigarettes”, “respiratory health and vape”, “respiratory diseases” (in Portuguese, English and Spanish). A direct association was observed between electronic cigarettes and injuries to the respiratory system, with the most characteristic illnesses being chronic inflammation, immunosuppression, lipoid pneumonia and chronic obstructive pulmonary disease (COPD), which includes bronchitis and pulmonary emphysema. The studies analyzed point to the relationship between the device and respiratory injuries due to inflammation and promotion of apoptosis of lung cells, which can trigger diseases of the pulmonary system, respiratory failure, neuromuscular damage and even death. Therefore, it can be concluded that electronic cigarettes are not safe and can be extremely harmful to health.